Modelling sector-specific employment shocks with EUROLAB, a multidimensional behavioural model - Edlira Narazani; Ugo Colombino (European Commission, Joint Research Centre (JRC), 2021)
Little is known yet about the impact of the COVID crisis on household income and jobs in absence of real time information on these variables. A recent literature strand has sought to overcome data limitations to assess the distributional impact of policy measures taken in the EU using various empirical approaches. However, despite the importance of behavioural effects, transitions from work to unemployment or inactivity (or vice versa) are considered exogenously in this literature. This paper explains how EUROLAB, a multidimensional discrete choice labour supply model, can be used to take account of behavioural effects in the face of exogenous demand shocks. We show that it is possible to account for behavioural effects endogenously using a procedure permitting a consistent introduction of sectoral demand shocks and the assessment of COVID-19 related reforms under equilibrium conditions. We illustrate the use of our model considering the case of a simplified wage subsidy scheme using Italian SILC. Our empirical results support the theoretical model, showing in particular how sectoral demand shocks lower wages, employment and increase unemployment under equilibrium conditions. Furthermore, the results show that the labour market reacts differently to the introduction of the wage subsidy scheme, depending on whether the wage subsidy is allocated to potential beneficiaries before or after labour market equilibrium is achieved. In the short-run, a wage subsidy helps to preserve jobs. From a longer-term perspective, it should contribute to the recovery of the labour market although the return to pre-shock employment level depends on a number of factors related to the subsidy (such as duration and amount) and the potential of the labour market to create new jobs.
Keywords: C35; J22; J23; J33; 330; Labour supply; Labour market equilibrium; Short-time work schemes; Covid-19